2010
DOI: 10.1016/j.jrp.2010.08.005
|View full text |Cite
|
Sign up to set email alerts
|

An attempt to validate national mean scores of Conscientiousness: No necessarily paradoxical findings

Abstract: Three large cross-cultural databases on personality were used to study the relationship between culture-level mean scores of Conscientiousness and 18 country-level criterion variables including health indicators, religiosity, democracy, corruption, economic wealth and freedom, and the presence of a favorable business environment. Mean Conscientiousness scores were significantly related to most of the criteria but different facets of Conscientiousness had very different relationships with external criteria. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 33 publications
2
39
1
Order By: Relevance
“…In contrast, these criteria were not associated with assessed Conscientiousness, and efforts to validate culture-level traits using collective behavioral indicators have had mixed success. Oishi and Roth (2008) found evidence for Agreeableness and Neuroticism, but not Conscientiousness; Mõttus, Allik, and Realo (2010) found some evidence for the criterion-related validity of Conscientiousness and its facets— although many predicted associations were not found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, these criteria were not associated with assessed Conscientiousness, and efforts to validate culture-level traits using collective behavioral indicators have had mixed success. Oishi and Roth (2008) found evidence for Agreeableness and Neuroticism, but not Conscientiousness; Mõttus, Allik, and Realo (2010) found some evidence for the criterion-related validity of Conscientiousness and its facets— although many predicted associations were not found.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between traits and outcomes is complex even at the individual level (e.g., Epstein, 1979), and likely to be much more so at the culture level (McCrae & Terracciano, 2008; Mõttus, Allik, & Realo, 2010), where group behaviors also reflect history, government policy, religion, climate, and so on. Judged by the synchronized watches, polished shoes, and disciplined marching on a military base, one might imagine that soldiers are especially high in Conscientiousness; this, however, is not the case (e.g., Jackson, Thoemmes, Jonkmann, Lüdke, & Trautwein, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Heine et al (2008) found indicators of high national Conscientiousness (e.g., postal workers' speed, per capita GDP, life expectancy) to be positively correlated with perceptions of national character, but negatively with national mean Conscientiousness scores. Mõttus, Allik, and Realo (2010), on the other hand, show that such correlations become more intuitive when explored at the facet level and make a case for the future of national mean comparisons. The interplay between traits and sociocultural context, however, means that measurement issues are complex.…”
Section: Agreeableness/antagonism Across Culturesmentioning
confidence: 97%
“…We are aware that, when two variables are strongly related at the cultural level, it does not automatically mean that the same mechanisms operate at the individual level (cf. Mõttus, Allik, & Realo, 2010), yet, due to the theoretical considerations noted above, we expect social capital (i.e., generalized social trust and informal social networks) to be positively related to individualism (i.e., Openness to Change) at the individual level in the same way the two constructs have repeatedly been shown to be associated at the cultural-level (Allik & Realo, 2004;Realo et al, 2008). In other words, we expect people who emphasize independence of thought, action, and feeling and readiness for change (in contrast to people who emphasize order, self-restriction, preservation of the past, and resistance to change) to be more willing to trust people beyond their nuclear family and kinship group, as well as to have more active and supportive informal social networks.…”
Section: The Aim Of the Present Studymentioning
confidence: 89%